Otimização em grafos no ensino básico - Carneiro, Rafael Dalvi (2018)
This work aims to present the number of graphs students in a more accessible and lower level of basic education. Theory of Graphs is a subject that is not presented formally in basic education in Brazil, but has a great facility in solving some problems related to Discrete Mathematics. In addition, Graph Theory is one of the main bases for computer programming. The work had an overview about graphs and some correlated concepts. Introduce Euler's Theorem, the paper discusses the trees and a count of trees. Subsequently, the work brings a discussion about tree optimization.